PELATIHAN GAMIFIKASI BAGI GURU DALAM MENDESAIN PEMBELAJARAN YANG MENARIK DI MTS SCI - Fuji Azzumar; Muhammad Ari Subhi; Budi Rianto; Muhammad Tareq Ghifari; Muhammad Aiman Jamil Lubis; Darhim (LPPM UNINUS, 2024)
Gamification in instruction is considered attractive to many students, thereby increasing motivation and learning engagement. The training carried out aims to provide teachers with experience in designing interesting instruction through Role-Playing Game Maker MV (RPG Maker MV 1.2.0). This article describes the implementation of gamification training for teachers at MTs Sekolah Cinta Ilmu (SCI), Bandung Regency. This activity is a form of community service carried out using preliminary surveys and practicum methods. The results of the activity show the teacher's enthusiasm for designing new instruction in the form of gamification. Various positive responses were conveyed by the teacher council participating in the training because, more or less, they had mastered the basic competencies in running the RPG Maker MV 1.2.0 application as a necessity for implementing innovative, creative, and interesting instruction.